Informal education in the system of public administration in the conditions of the COVID19 pandemic and the war in Ukraine - Khozhylo, I. I.; Lipovska, N. A.; Antonova, O. V. (Baltija Publishing, 2023)
The growing public demands on the activities of persons serving the public interest are particularly acute at the level of local government. In the context of significant transformational changes in the functioning of public administration (the public administration reform and local self-government reform), and a number of sectoral reforms (medical, educational, land reforms) in Ukraine, there is a strengthening of democratic foundations for activities of local self-government bodies, which is largely reflected in the introduction of various forms of active citizen participation in local self-government. On the other hand, the reform of local self-government revealed certain contradictions between the declared intentions and the results of decentralization of power. This contradiction is at the heart of the issue of division of powers and provision of adequate resources. This is especially acute in the health sector. Such inconsistencies make it difficult to fulfill the tasks, health care issues among them, for local self-government bodies including deputies of local councils as representatives of the interests of the territorial communities, voters in their constituencies.
Keywords: public administration; COVID-19; informal education; health care; anti-epidemic measures; self-education